1044 Impact of Obesity on Complications from Anterior Lumbar Interbody Fusion. (12th October 2021) - Feeley, A; Feeley, I; Butler, J
Abstract: Aim: Anterior Lumbar Interbody Fusion is a procedure growing in popularity for conditions including degenerative disc disease, and discogenic back pain. Obesity is a significant risk factor in the development of back pain, with patients with raised BMIs at increased of complications using the posterior approach. This review aims to evaluate the risk profile of this patient cohort using the anterior approach for lumbar interbody fusion. Method: A systematic review of the search databases Pubmed; google scholar; and OVID Medline was carried out between September 2020-November 2020. Studies evaluating the risks associated with obesity during Anterior Lumbar Interbody Fusion (ALIF) were identified and included for review according to PRISMA guidelines. Studies eligible for inclusion were agreed by two independent reviewers. Meta-analysis was used to compare intra- and postoperative complications in patients with increased BMI during ALIF. Results: Search terms yielded 435 articles for evaluation. 13 studies were included in this review after applying inclusion and exclusion criteria. Meta-analysis of studies demonstrated a significantly increased risk profile for overall complications in the obese patient cohort (CI = 0.04-0.16, p = 0.002) with significant heterogeneity (I 2 =86%). Patients with increased BMI were not significantly more likely to develop Vascular complications (CI= -.03-0.02, p = 0.62). Simple pooling demonstrated significant association between increased BMI and blood loss. Conclusions: Obesity was demonstrated to have an impact on overall complication rates in Anterior Lumbar Interbody Fusion procedures, with postoperative complications including wound infections and lower fusion rates more common in patients in increased BMIs.